A Review on Degree, Order and Size of Single-Valued Quadripartitioned Neutrosophic Graphs (BISTUA Revista de la Facultad de Ciencias Básicas, 2022)
In this article an attempt is made to introduce and study the concept of single-valued quadripartitioned neutrosophic graph (SVQN-graph) by extending the idea of single-valued neutrosophic graph (SVN-graph) theory. Besides, we introduce the notion of degree, order and size of SVQN-graphs. Further, we furnish few illustrative examples to justify the results.
Keywords: SVNS; SVN-graph; SVQN-graph; SVQN-set.